Design of Large Scale Log Analysis Studies - Dumais, Susan; Jeffries, Robin; Russell, Daniel M.; Tang, Diane; Teevan, Jaime (2010)
Design of Large Scale Log Analysis Studies: A short tutorial.
HCIC 2010